EKSPERIMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH DAN PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KREATIVITAS SISWA KELAS VIII SMP NEGERI Se-KABUPATEN PACITAN TAHUN PELAJARAN 2013/2014 - Aini, Harmei Mahar’; Mardiyana, Mardiyana; Sari S, Dewi Retno (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aim of the research was to determine the effect of learning models viewed from the creativity of student. The learning models compared were PBL, TPS and direct learning. This research is a quasi experimental with the factorial design of 3x4. The research population was 8th Grade of Junior High School first semester of 2013/2014 at Pacitan regency. The sampling technique using a stratified cluster random sampling. Samples in this research were 260 students with 84 students as experimental class I, 88 students as experimental class II and 84 students as control class. Hypothesis testing was performed using two-way analysis of variance with unequal cells. Based on the results of hypothesis testing were concluded that: (1) PBL learning model gave better achievement than TPS learning model and direct learning, while TPS learning model and direct learning gave the same achievement (2) The learning achievement of students with high creativity is better than the students with medium and low creativity, and the learning achievement of students with medium creativity is better than the students with low creativity (3) on each category of creativity, PBL learning model gave better achievement than TPS learning model and direct learning, while TPS learning model and direct learning gave the same achievement, (4) on each models of learning, learning achievement of students with high creativity is better than the students with medium and low creativity, and the learning achievement of students with medium creativity is better than the students with low creativityKeywords: Problem Based Learning (PBL), Think Pair Share (TPS), Creativity of student